Guildas de Tetraodontiformes (Teleostei, Acanthopterygii) em um complexo estuarino tropical - Andrade, Amanda Carvalho de (Universidade Federal de São Carlos, 2009)
The demersal ichthyofauna of Guanabara bay was sampled bimonthly, during two years, in ten stations distributed along a hydrobiological gradient. An otter trawl was employed, conducting 30 minute trawls, at a speed of 2 knots, summing up to 240 hours of fishing effort from July 2005 to June 2007. A total of 16,081 Tetraodontiformes specimens were collected, representing ten species divided among the families Ostraciidae, Monacanthidae, Tetraodontidae and Diodontidae. The otter trawl was considered an adequate technique to sample the group, although it may underestimate the abundances of species associated with hard bottoms (Acanthostracion sp.) and marginal areas (Sphoeroides spp.). Tetraodontiformes fishes appear to be well adapted to hydrological variations and to inhospitable conditions prompted by intense eutrophication. However, abiotic factors traditionally considered important in the structuring of estuarine communities play a secondary role in regulating the distribution of Tetraodontiformes. The type of sediment appears as the most important physical factor, but acts only as an indicator of ecological domain. The low explicability of physical-chemical variables, in addition to the relative stability of the bay s ichthyofauna, suggests the influence of biological parameters. The main biological factors related with the ichthyocenosis seasonal variations are food items availability, intra- and interspecific competition and the species reproductive cycles. Tetraodontiformes exhibited a wide variation of uses in Guanabara bay, utilizing it as a resting, feeding and growing area. However, it was not possible to establish a relation of dependence upon the estuary for any of the species, because the same population strata occur the in coastal regions of South-Southeastern Brazil. Among the ten species of Tetraodontiformes captured, eight were categorized as marine estuarine opportunists and two as marine stragglers. Chilomycterus spinosus population boom indicated an ecological misbalance and must be carefully investigated. Subsequent studies should adopt a population approach of these species and attempt to elucidate the relationships between estuarine and marine stocks.
Keywords: Ecologia da população; Distribuição espacial; Distribuição sazonal; Ictiofauna; Estuário; Guanabara, Baía de (RJ); Abundância; Distribution; Abundance; Diversity; Ichthyofauna; Estuary; Guanabara bay; CIENCIAS BIOLOGICAS::ECOLOGIA